2015
DOI: 10.1177/1933719115584448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pazopanib, Sunitinib, and Sorafenib, Anti-VEGF Agents, on the Growth of Experimental Endometriosis in Rats

Abstract: We aimed to compare the effects of pazopanib, sunitinib, and sorafenib on endometriotic tissue morphology and histological characteristics as well as ovarian reserve in a rat model. Experimental endometriosis was established in 32 rats. They were randomly divided into 4 groups (8 rats for each group) to administer study drugs: pazopanib, sunitinib, sorafenib, and normal saline. Histological examination with hematoxylin and eosin staining to determine endometriosis score and immunostaining with primary vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
0
36
1
Order By: Relevance
“…We screened the 135 full publications and excluded an additional 122 publications for the following reasons: 54 combined anti-angiogenesis therapy effects; 13 were cell studies; 4 duplicate publications; 37 reviews; 4 with no relevant outcomes; 8 were not relevant to endometriosis; 1 model was significantly different from the other studies; and 1 had no obtainable concrete data. Finally, the present systematic review included 13 articles comprising 16 animal experiments with 245 animals, published between January 1995 and June 2016, which met the inclusion criteria [1628] (Table 1). The characteristics among these studies varied considerably.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened the 135 full publications and excluded an additional 122 publications for the following reasons: 54 combined anti-angiogenesis therapy effects; 13 were cell studies; 4 duplicate publications; 37 reviews; 4 with no relevant outcomes; 8 were not relevant to endometriosis; 1 model was significantly different from the other studies; and 1 had no obtainable concrete data. Finally, the present systematic review included 13 articles comprising 16 animal experiments with 245 animals, published between January 1995 and June 2016, which met the inclusion criteria [1628] (Table 1). The characteristics among these studies varied considerably.…”
Section: Resultsmentioning
confidence: 99%
“…Endometriosis score outcomes after anti-VEGF/VEGFR therapy were reported in 9 experiments [20, 22, 23, 2628]. Taken together, these experiments showed that anti-angiogenesis intervention was associated with a lower endometriosis score (SMD –1.17, 95% CI –1.65 to –0.69; P < 0.0001) with a large heterogeneity in the estimates (I 2 = 50.3%, 95% CI 0% to 77%; H 2 = 1.01; Fig 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Sunitinib was able to decrease the endometriotic implant volume and adhesion level in an experimental animal model, presumably by inhibiting VEGFR and enhancing apoptosis [159,163]. When various multitargeted TKIs were compared, each seemed to have a different effect on endometriosis extent, VEGF expression, and CD117 expression [164]. Pazopanib and sunitinib significantly reduced endometriotic lesions, whereas sorafenib had no significant effect [164].…”
Section: Targeting Inflammation For Treatment Of Endometriosis-assmentioning
confidence: 99%
“…When various multitargeted TKIs were compared, each seemed to have a different effect on endometriosis extent, VEGF expression, and CD117 expression [164]. Pazopanib and sunitinib significantly reduced endometriotic lesions, whereas sorafenib had no significant effect [164]. Three drugs (pazopanib, sunitinib, and sorafenib) reduced VEGF expression but only pazopanib and sunitinib reduced CD117 expression [164].…”
Section: Targeting Inflammation For Treatment Of Endometriosis-assmentioning
confidence: 99%
See 1 more Smart Citation